Evidence for significant granite creation by the ballooning mechanism: The example of the Ardara pluton, Ireland - Molyneux, S; Hutton, D (2000)
The emplacement mechanism of the Ardara granite (a Caledonian pluton located on the northwestern seaboard of Ireland) has been a widely cited and a key point of reference in the debate about the granite space problem for nearly half a century. Early models related its subcircular tailed shape, concentric foliation pattern, and concentrically deformed envelope to diapirism. It was subsequently reinterpreted, using strain data, as a ballooning pluton that was created by ∼70% in situ expansion at the emplacement site and was later cut by a regional shear zone. Recently it was the leading example in a wide-ranging review of forcefully emplaced plutons of this type and was reinterpreted as a series of nested diapirs associated with only modest amounts (30%) of forceful space creation, but a large component of inferred early block stoping. We report the results of the complete remapping and extensive collection of new structural data from this 8-km-diameter, normally zoned, three-phase, calc-alkaline pluton. We confirm the existence of the steeply inclined internal foliation pattern and that it was formed in the magmatic state, although this and the outline of the pluton are modified by late-stage (high temperature solid state) regional transcurrent shear zones along two of the pluton contacts. Structural mapping has failed to identify a macroscopic lineation in the magmatic foliation planes, and this is confirmed by strain determinations (using mafic enclave populations and magmatic crystal separations) for the magmatic state deformation that show nearly pure flattening type strains (K = 0). Strains measured by these techniques show an apparently smooth gradient increasing outward toward the pluton contacts from an inner low-strain zone. We argue that these features, together with the simple normal petrographic zonation, a lack of small-scale structures that would indicate the pluton had moved up relative to the wall rocks, and an exposure level that is not in the roof zone, are inconsistent with diapirism (either singly, or multiply) but are most easily explained by a ballooning emplacement mechanism. Synmagmatic shear-sense data from both the pluton and the adjacent country rocks indicate, however, that within the overall context of radial ballooning there was a limited amount of late-stage nonradial (northward) injection of magma. An inversion of the deformed enclave and crystal spacing strain determinations and strain determinations within the country rocks suggest that more than 80% of the volume of the pluton was accommodated by the ballooning mechanism.